Green roof on tropical house as architectural innovation responding Covid-19 pandemic - Sri Yuliani; Ana Hardiana; Amin Sumadyo; Tri Yuni Iswati (ARTEKS : Jurnal Teknik Arsitektur, 2022)
Green roof researches have many benefits in supporting a sustainable environment. During the covid-19 pandemic, there was a change in lifestyle due to demands for the prevention of transmission, so many activities were carried out at home. These two phenomena will be integrated into this study, to provide solutions for space expansion in residential areas during the covid-19 pandemic. The research method uses an online questionnaire in several regions in Indonesia and a small number outside Indonesia; conducting a content analysis on previous green roof research; then linking the results of community responses and the potential for green roofs. The results of the study found that there were still few people who knew about the opportunity for a roof to expand its space which was more useful, even though there have been many findings of green roof innovations. In addition, there is still little research on green roofs that relates to the pandemic situation, particularly in Indonesia.